Dye-Sensitized Solar Cells Characterization of Kitolod Leaves (Hippobroma longifora) - Rohmah, Roihatur; Yuwita, Pelangi Eka; Pangestu, Prayoga Dewa; Vibianto, Erlangga Dwi Aprila (Department of Physics Education, Universitas Mataram, 2024)
Energy from fossil fuels is decreasing day by day and also causes many environmental problems. In the current era, many environmentally friendly renewable energy sources have been developed, such as the development of DSSC (Dye Sensitized Solar Cells). DSSC is a technology that utilizes colored materials sourced from nature which are used as absorbers of sunlight energy to be converted into electrical energy. In this research, the synthesis and characterization of organic material from kitolod leaves as DSSC will be carried out. Kitolod leaves (Hippobroma longifora) are wild plants that usually grow in home gardens and rice fields. Kitolod leaves which have chlorophyll can support the absorption of sunlight if applied as a sensitizer in DSSC. The methods that will be used in this research are making TiO2 paste, dye solution preparation, electrolyte solution preparation, DSSC fabrication, testing and characterization. The tests that will be carried out are testing the TiO2 layer, dye absorption, and electric current. Meanwhile, the characterization that will be carried out is dye absorption using UV-Vis, and electric current using a potentiometer. From the results of light absorption shows that when the wavelength is 500 nm or the green light spectrum, the maximum light absorption by the chlorophyll of kitolod leaves is 1.78 (a.u.). The maximum voltage (Vm) and maximum current (Im) in daylight lamps have greater values ​​compared to warm white lamps. The highest efficiency of the solar light source is shown when the air mass is 1.5 (08.30-08.40). The time of DSSC immersion in dye also influences the resulting of Vm and Im values ​​which can be shown in that the Vm and Im values ​​of DSSC 2 (30 minutes) are greater than those of DSSC 1 (10 minutes). The results of open circuit voltage (Voc) and the short circuit current (Isc) in this research still need to be improved to produce better efficiency.